1999
DOI: 10.1002/(sici)1097-4652(199902)178:2<173::aid-jcp6>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation‐promoting effect of 1‐O (2 methoxy) hexadecyl glycerol in human colon cancer cells

Abstract: Alkylglycerols are naturally occurring bioactive ether lipids found in great abundance in the livers of many marine species. In this study, we evaluated the differentiation-promoting potential of a methoxy substituted alkylglycerol--1-O (2 methoxy) hexadecyl glycerol (MHG)--to promote a more benign or differentiated phenotype in human colon cancer cells. Three cell lines with different biological and phenotypic properties were used. They were the moderately differentiated and growth factor-responsive Moser, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…16 HCT116 is a poorly differentiated and growth factor-insensitive cell type that is, however, responsive to various cellular stresses, including DNA damage and spindle disruption. 16,17 HCT116 cells and the p53-negative derivatives were grown in culture with an approximately equal doubling time (30 hr). Incubation with resveratrol at concentrations between 10 and 100 M resulted in the appearance, under the electron microscope and the light microscope after DAPI staining, of condensed nuclei and apoptotic bodies as early as 24 hr after treatment, regardless of p53 status (data not shown).…”
Section: Induction Of P53-independent Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…16 HCT116 is a poorly differentiated and growth factor-insensitive cell type that is, however, responsive to various cellular stresses, including DNA damage and spindle disruption. 16,17 HCT116 cells and the p53-negative derivatives were grown in culture with an approximately equal doubling time (30 hr). Incubation with resveratrol at concentrations between 10 and 100 M resulted in the appearance, under the electron microscope and the light microscope after DAPI staining, of condensed nuclei and apoptotic bodies as early as 24 hr after treatment, regardless of p53 status (data not shown).…”
Section: Induction Of P53-independent Apoptosismentioning
confidence: 99%
“…Scanning and transmission electron microscopy revealed that in HCT116 cells the ultrastructural features of differentiation are only weakly developed, in accord with previous findings indicating the poor differentiation of this cell type. 17 However, by 24 hr after resveratrol treatment and regardless of p53 status, cells had begun to assume a morphology resembling that of columnar absorptive cells, with an increase in size, a more polygonal shape, the development of a dense apical brush border and the arrangement of cells in tight contact with the appearance of desmosomes (Fig. 6a).…”
Section: Epithelial Differentiation At Early Times During Resveratrolmentioning
confidence: 99%
“…Ectopic expression of the PAF receptor in normal rat kidney mesenchymal fibroblasts, however, has been reported to suppress v-src-or v-ras-induced transformation (Kume and Shimizu, 1997). We had earlier shown that 1-O(2-methoxy) hexadecyl glycerol, a lipid with similar aliphatic fatty acid chains to that of PAF is biologically active and suppresses the malignant properties of human colon and prostate cancer cells (Wang et al, 1999;Reynolds et al, 2000). In this study, we showed that PAF-activated MAP kinases, induced a more differentiated phenotype and suppressed the malignant properties of human colon carcinoma cells.…”
mentioning
confidence: 99%
“…(a) PAF and cellular proliferation. Cellular proliferation was determined by the MTT assay in 96-well culture plates as described previously (Wang et al, 1999). Briefly, cells were seeded into 96-well culture plates (200 ml per well at a density of 20 000 cells/ml) and allowed to attach overnight.…”
mentioning
confidence: 99%
See 1 more Smart Citation